2014
DOI: 10.17221/7385-vetmed
|View full text |Cite
|
Sign up to set email alerts
|

Combined surgical and endoscopic approach for the reduction of a congenital hiatal hernia in a cat: a case report

Abstract: A case of surgical resolution of type I or "sliding" hiatal hernia is reported. A seven-month-old kitten was presented because of abdominal discomfort, accelerated breathing after eating and chronic vomiting. The clinical examination was unremarkable. Thoracic radiographs and gastroscopy led to the diagnosis of type I hiatal hernia. The surgical resolution consisted of hiatal plication, oesophagopexy and left-flank incisional gastropexy. All procedures were carried out using a 6 mm videoendoscope positioned in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…A second surgery which included an oesophagopexy was performed a week later, which resulted in a positive outcome. These authors suggested that an oesophagopexy was an essential part of the surgical management of a sliding hiatal hernia (Pisoni and others 2014). Due to the conflicting information within the literature, a phrenicoplasty, oesophagopexy and gastropexy were performed in this case study to reduce the risk of postoperative complications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A second surgery which included an oesophagopexy was performed a week later, which resulted in a positive outcome. These authors suggested that an oesophagopexy was an essential part of the surgical management of a sliding hiatal hernia (Pisoni and others 2014). Due to the conflicting information within the literature, a phrenicoplasty, oesophagopexy and gastropexy were performed in this case study to reduce the risk of postoperative complications.…”
Section: Discussionmentioning
confidence: 99%
“…The degree to which the hiatus should be closed is another contentious issue surrounding the surgical repair of a hiatus hernia. There are unfortunately no clear guidelines or set standards for hiatal diameter and clinical judgement is generally used to determine the appropriate size (Sivacolundhu and others 2002, Pisoni and others 2014). Some reports advise aiming for a hiatal diameter of 1–2 cm, while others suggest that the hiatus should allow one or two fingers to pass through intraoperatively (White 1993).…”
Section: Discussionmentioning
confidence: 99%